Identification And Diversity Of Lichen Species In Lake Leonard, New Leyte, Maco, Davao De Oro Province - Princes Luise Dela Tina- Picaza; Rholey Ramos Picaza (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to collect, classify, and identify lichens found in Lake Leonard, New Leyte, Maco, and Davao de Oro Province. Field surveys and sample collection were carried out through the transect walk method. The lichen species were collected using a knife and then placed inside resealable plastic bags. The collected specimens were air dried and then placed on herbarium packets with detailed taxonomic information. The collected specimens were preserved. Out of thirty-five (35) specimens collected, Thirty-three (33) species of lichens were identified. Nineteen (19) genera and twelve (12) families, namely: Pertusariaceae, Physciaceae, Parmaliaceae, Collenmataceae, Graphidaeceae, Cladoniaceae, Teloschistaceae, Coccoatpiaceae, Ramalinaceae, Hygrophoraceae, Thelotremataceae, and Sterocaulaceae Most of the collected species in the study area were rare (73%). Only a few were found widespread in the study area. This result could serve as baseline data for the management of the lichen ecosystem in the area.